2023
DOI: 10.1002/ptr.7782
|View full text |Cite
|
Sign up to set email alerts
|

Danggui Buxue Tang potentiates the cytotoxicity of 5‐fluorouracil on colorectal adenocarcinoma cells: A signaling mediated by c‐Jun N‐terminal kinase

Abstract: Danggui Buxue Tang (DBT) is a well-known Chinese herbal recipe often prescribed in clinical treatment for menopausal and cardiovascular symptoms. 5-Fluorouracil (5-FU) is a chemotherapy drug that treats several cancers; however, it causes severe adverse effects and multidrug resistance. Combining natural medications can reduce the side effects of 5-FU use. Hence, we aimed to determine the role of DBT in strengthening the anticancer capabilities of 5-FU in a cultured colorectal adenocarcinoma cell line (HT-29 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Danggui Buxue Tang, a traditional herbal formula composed of Astragali Radix and Angelica Sinensis Radix , recorded in “Neiwaishang Bianhuo Lun” published in 1247, has been reported to significantly enhances apoptosis and reduce tumor weight and volume in colorectal cancer cells when combined with 5-FU. 39 This effect seems to be associated with increased phosphorylation of JNK and C-Jun.…”
Section: Resultsmentioning
confidence: 98%
“…Danggui Buxue Tang, a traditional herbal formula composed of Astragali Radix and Angelica Sinensis Radix , recorded in “Neiwaishang Bianhuo Lun” published in 1247, has been reported to significantly enhances apoptosis and reduce tumor weight and volume in colorectal cancer cells when combined with 5-FU. 39 This effect seems to be associated with increased phosphorylation of JNK and C-Jun.…”
Section: Resultsmentioning
confidence: 98%
“…Blood deficiency syndrome (BDS) is a fundamental syndrome in traditional Chinese medicine (TCM) and is caused by insufficient blood and excessive consumption (Sun et al, 2022). The incidence of BDS is predicted to increase dramatically, leading to detrimental health effects including headaches, weakened immune systems, and infertility (Huang et al, 2020;Wang et al, 2021;Gong et al, 2023). Although blood transfusion is the current clinical therapy, it may lead to allergic reactions and gastrointestinal discomfort, and BDS may recur upon discontinuation of treatment (Kurihara et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous clinical studies have found that TCM combined with chemotherapy in the treatment of CRC may improve clinical symptoms, enhance immunity, and alleviate chemotherapy-induced adverse reactions. 8 - 10 Compound Kushen injection (CKI) is one of the representative and effective Chinese patent medicines, which is extracted from 2 medical herbs: Kushen ( Sophora flavescens Ait.) and Baituling ( Smilax glabra Roxb.).…”
Section: Introductionmentioning
confidence: 99%